Taksiran Berat Janin Berdasarkan Analisis Perilaku, Dukungan Keluarga dan Sarana - Susilawati Susilawati; Nur Alam Fajar; Hamzah Hasyim (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze pregnant women's behavior, family support, and facilities on the estimated fetal weight in Kepahiang District. The research method used is descriptive-analytic research with a cross-sectional approach. The sampling process used the purposive sampling technique. The results showed that the majority of respondents with a good level of knowledge consisted of 54 people (64.3%); 47 respondents had a negative attitude (56%); respondents with sufficient action are 37 people (44.0%); respondents who received good family support were 54 people (64.3%); 60 respondents use public transportation to health services (71.4%); and respondents who had an abnormal estimated fetal weight (TBJ) were 61 people (72.6%). In conclusion, the attitude variable was the dominant factor in the incidence of estimated fetal weight in the Kepahiang Regency in 2021. Keywords: Family Support, Pregnant Women, Behavior, Means, Estimated Fetal Weight